THE EFFECT OF EXTERNAL AND INTERNAL FACTORS ON FINANCIAL PERFORMANCE OF ISLAMIC BANKING - Fahlevi, Mochammad; Surtinah, Wiwin; Firmansyah (STIE Kusuma Negara, 2019)
Research on the sharia bank financial performance level was first conducted by SudinHaron (1996), then similar research was conducted by Anna P.I. Vong(1997), M. Kabir Hassan (2002), Abdel-Hameed M. Bashir (2003), Samy Ben Naceur (2003), Muhammad Farhan, Khizer Ali and ShamaSadaqat (2011), and Nor Hayati Ahmad (2011). Macroeconomic factors and internal factors are variables that have an effect on sharia banking. These factors are GDP, inflation, and interest rates, FDR, OER which can affect directly or indirectly the financial performance of sharia banks in Indonesia. The result has shown GDP has a significant positive effect on ROA, it is match with several previous research, Inflation has no significant and negative effect on ROA, because when inflation central bank will give policy to increase BI rate, and sharia bank doesn?t effect with interest rate because interest is riba, interest rate has no significant effect on ROA because sharia bank doesn?t effect with the interest but use profit and loss sharing to financing, so in macroeconomic the result only GDP has significant and positive effect on ROA. The result has shown FDR has no significant effect on ROA, but has positive effect and the result match with previous research in relationship FDR and ROA, OER has negative significant effect on ROA and match with previous research (Sianturi, 2013).